Enzyme‐triggered fluorescence turn‐off/turn‐on of carbon dots for monitoring β‐glucosidase and its inhibitor in living cells. (11th November 2019) - Kong, Bo; Yang, Tong; Hou, Peng; Li, Chun Hong; Zou, Hong Yan; Huang, Cheng Zhi
Abstract: Energy transfer engineering based on fluorescent probes for directly sensing enzyme activities are in great demand as enzyme‐mediated transformations, which are central to all biological processes. Here, a fluorescence carbon dot (CD)‐based assay exhibiting selective responses to the quantitation of β‐glucosidase and the effect of its inhibitor was developed. The most common substrate, para‐nitrophenyl‐β‐d ‐glucopyranoside (pNPG) was hydrolyzed by β‐glucosidase to release p ‐nitrophenol (pNP), which can efficiently quench fluorescence of CDs via an inner filter effect and electron transfer. However, in the presence of inhibitors of β‐glucosidase, the fluorescence intensity gradually recovered as the concentration of inhibitors increased. Therefore, the enzyme‐triggered fluorescence turn‐off/turn‐on of specific CDs successfully achieved sensitive detection of β‐glucosidase and monitored the effect of its inhibitors. This new strategy was applied to detect β‐glucosidase and monitor β‐glucosidase inhibitor in hepatoma cells using cell imaging. All results suggest that the new method is sensitive and promising for use in cancer diagnosis and treatment.